Correction: A single-center retrospective cohort study of perioperative systemic chemotherapy in diffuse malignant peritoneal mesothelioma. - PLOS ONE Editors (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0275187.].